2018
DOI: 10.1111/1556-4029.13893
|View full text |Cite
|
Sign up to set email alerts
|

Understanding (Mis)classification Trends of Latin Americans in Fordisc 3.1: Incorporating Cranial Morphology, Microgeographic Origin, and Admixture Proportions for Interpretation

Abstract: Assigning correct population affinity to a skeleton can contribute important information to an investigation-yet recent work highlights high error rates when classifying Latinos with a traditional tool, Fordisc 3.1 (FD3). Our study examines whether misclassification trends exist, and whether these can be used to infer population affinity. We examine the relationships among ancestry, geography, and FD3 misclassifications of Latinos using canonical variate analysis and unsupervised model-based clustering of cran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…This framing was particularly important in understanding the designation of ‘Hispanic’ in a Tudor context. This classification is used in the USA and refers to individuals with origins or ancestral connections to Spanish-speaking regions, particularly from the Americas [ 103 , 104 ]. Applying this linguistic and social distinction to physical remains is practically and ethically challenging, and requires an understanding of the colonialist practices in ‘Hispanic’ regions, which ultimately led to an admixture of Indigenous populations, (enslaved) African and European settlers [ 104 ].…”
Section: Methodsmentioning
confidence: 99%
“…This framing was particularly important in understanding the designation of ‘Hispanic’ in a Tudor context. This classification is used in the USA and refers to individuals with origins or ancestral connections to Spanish-speaking regions, particularly from the Americas [ 103 , 104 ]. Applying this linguistic and social distinction to physical remains is practically and ethically challenging, and requires an understanding of the colonialist practices in ‘Hispanic’ regions, which ultimately led to an admixture of Indigenous populations, (enslaved) African and European settlers [ 104 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Guatemalan Mayan sample was collected from FAFG and represents predominantly Mayans (n = 87 male) from rural areas of Comalapa and Rabinal (Hughes et al, 2019;Spradley et al, 2008).…”
Section: Data From Us/mexico Border Casework Comes From the Pimamentioning
confidence: 99%
“…The Guatemalan sample is a relatively homogeneous sample of contemporary Indigenous Mayans with little European admixture (Hughes et al, 2019;Spradley et al, 2008). The Hispanic sample is more heterogeneous and comprised primarily but not exclusively of migrants who died in Arizona (Hughes, Dudzik, & Algee-Hewitt, 2017;Spradley et al, 2005). Most of the Hispanic cases were only contextually identified (Jantz & Ousley, 2005) based on their circumstances surrounding death, including the biocultural profile (Anderson, 2008;Birkby et al, 2008 OpID, make it possible to begin testing if currently available and widely used reference data are the most appropriate for all migrants found along the entire US/Mexico border.…”
mentioning
confidence: 99%
“…Only recently have studies sought to produce information estimation criteria for individuals of Mexican nationality. Yet, they have been constrained to the study of sex and ancestry using metric skeletal data from positively identified US-Mexico border crosser fatalities (Fowler and Hughes 2018;Hughes et al 2018;Ross et al 2014;Spradley et al 2015;Spradley et al 2008;Tise et al 2013). Due to the small numbers and lack of demographic information (i.e., true age) for these highly targeted analyses, other parameters requiring osteological estimation, such as age-at-death have not been thoroughly examined and validated against the most well-established aging techniques even for these samples.…”
mentioning
confidence: 99%